2017
DOI: 10.1111/1365-2478.12485
|View full text |Cite
|
Sign up to set email alerts
|

Determination of moment tensor and location of microseismic events under conditions of highly correlated noise based on the maximum likelihood method

Abstract: We examine the problem of localization of a single microseismic event and determination of its seismic moment tensor in the presence of strongly correlated noise. This is a typical problem occurring in monitoring of microseismic events from a daylight surface during producing or surface monitoring of hydraulic fracturing. We propose a solution to this problem based on the method of maximum likelihood. We discuss mathematical aspects of the problem, some features and weak points of the proposed approach, estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…5 outlines the main processes of the workflow that leads to the location of a microseismic event. More broadly speaking, the relatively integrated procedures consist in identification of effective events on the microseismic records, selecting the arrival times of the P and S waves, deriving an approximate velocity model and source location that particularly is considered to be of paramount importance and a challenge in monitoring (Birialtsev et al, 2017;Soledad and Danilo, 2018). In other words, to better delineate fracture distribution, reliable locational algorithmic studies are extremely urgent.…”
Section: Microseismic Monitoring Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…5 outlines the main processes of the workflow that leads to the location of a microseismic event. More broadly speaking, the relatively integrated procedures consist in identification of effective events on the microseismic records, selecting the arrival times of the P and S waves, deriving an approximate velocity model and source location that particularly is considered to be of paramount importance and a challenge in monitoring (Birialtsev et al, 2017;Soledad and Danilo, 2018). In other words, to better delineate fracture distribution, reliable locational algorithmic studies are extremely urgent.…”
Section: Microseismic Monitoring Techniquementioning
confidence: 99%
“…These events launch waves into the surrounding medium and can be recorded by geophones installed in a borehole or near the surface (Zhang et al, 2013;Zhang et al, 2016;Meng et al, 2018). Associated with hydraulic fracturing processes, microseismic monitoring helps in understanding the geometric shapes of the induced fractures as well as resource characterization and estimation of the process effect of fracturing technology (Birialtsev et al, 2017;Woo and Kang, 2017;Soledad and Danilo, 2018;Alfataierge et al, 2019). In addition, the downhole microseismic monitoring we focus on in this work more approaches reservoirs, gaining wider recognition because of its advantages of high signal-tonoise values (S/N ratio), well developed P and S waves, and so on (Maxwell et al, 2010;Jones et al, 2014;Yuan and Li, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For the moment tensor inversion, the contamination of noise can hardly be avoided [19], and the inversion results are inaccurate. To improve inversion accuracy, a channel selection approach [20][21][22] can be implemented, where the waveforms with insufficient signal-tonoise ratios (SNRs) are discarded to directly reduce the effect of noise on inversion accuracy. The channel selection approach is efficient, but a large number of sensors are needed for data recording.…”
Section: Introductionmentioning
confidence: 99%
“…() also showed that statistically optimal algorithms (maximum likelihood method) perform better than SET in the presence of man‐made surface noise during hydraulic fracturing. Birialtsev, Demidov and Mokshin () proposed a similar approach to reconstruct the seismic moment tensor. Birialtsev et al .…”
Section: Introductionmentioning
confidence: 99%